(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Внесение (3-10%) муки из семян тыквы способствовало увеличению количества клейковины теста на 8,5-16,0%. При этом достигнуто улучшение качества клейковины. С внесением в тесто тыквенной муки обеспечена улучшение её реологических свойств. The introduction (3-10 %) of pumpkin seed flour contributed to an increase in the amount of gluten dough by 8,5-16,0 % , while the quality of gluten was improved by adding pumpkin flour the dough, and it’s rheological properties were improved.